Ozone therapy and weight loss: An integrative literature review of Brazilian productions (Research, Society and Development, 2024)
This investigation aims to conduct an integrative review of the literature on the use of ozone therapy in the context of weight loss, examining its efficacy, mechanisms of action, and safety. Employing a rigorous methodology, the review focused on formulating a guiding question to direct the search in electronic databases such as Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO), PubMed, and Google Scholar. Initially, 421 potentially relevant publications were identified. After a thorough screening based on titles and abstracts, 39 works were pre-selected. Of these, 11 were excluded for not meeting the established time limit for the study. Subsequent analysis of the inclusion criteria resulted in the final selection of 5 pertinent studies for this investigation. The results of the review highlight that ozone therapy, especially its lipolytic effect – the ability to break down fat cells – plays a crucial role in weight loss. This mechanism not only contributes to the reduction of adiposities but also positively influences overall metabolism. Moreover, the versatility of ozone therapy in various clinical conditions was evidenced, reflecting its applicability as a comprehensive treatment modality. It is concluded that ozone therapy emerges as a promising option in the treatment of weight loss, given its capacity to influence critical factors such as lipolysis and metabolism. This integrative review sheds light on the therapeutic potential of ozone therapy in the context of weight loss, suggesting a fertile field for future research and clinical applications.